Differences in forming mechanisms and mechanical properties between LPBF and DED processed highland gabbro lunar soil simulants - Peng Chen; Lu Zhang; Zhao Hu; Huajun Sun; Chengao Jiang; Kai Liu; Chunze Yan; Yusheng Shi (Virtual and Physical Prototyping)
Laser powder bed fusion (LPBF) and directed energy deposition (DED) are effective technologies for customised lunar construction; however, the essential differences in technological principles and forming mechanisms for processing highland gabbro lunar soil simulants remain unclear. Therefore, the mechanism analysis for processing gabbro lunar soil simulants and the microstructure difference between the two methods are thoroughly studied in this article, and their effects on nano-mechanical properties are clarified. Compared with the DED process, LPBF has the obvious characteristic of layer-wise accumulation of roughness, which directly affects the stability and continuity of powder spreading. With the same laser energy input, the components processed by LPBF have higher nano-mechanical properties, of which the elastic modulus, hardness, and fracture toughness can reach 95.03, 8.91 GPa, and 104807439.8 Nm−3/2, respectively. This can be attributed to the LPBF LPBF-processed components have a higher degree of high-frequency shift and a more closely arranged crystal plane, and thus, higher structural stability. Meanwhile, the chain structure of pyroxene or amphibole was transformed into a quartz amorphous structure and a small amount of feldspar. This study provides theoretical support for the development of highland in-situ additive manufacturing.